Pemberatan Pidana dalam Tindak Pidana Kekerasan Seksual Terhadap Penyandang Disabilitas (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to analyze legal protection for persons with disabilities as victims of sexual violence and the best formulation of criminal sanctions for perpetrators of sexual violence against persons with disabilities. The research method used in this study is normative juridical research with a problem approach, namely the statutory approach, the conceptual approach, and the case approach. Having a disability status in Indonesia has not been fully accepted and appreciated by other normal humans. They are still considered different and are often bombarded with insults and inappropriate behavior such as sexual violence. The results of the study show that the high number of victims of sexual violence among persons with disabilities ranges from adolescence to various genders. Then the DPP PPDI stated that they seemed to be walking alone in fighting for justice for the weak position of persons with disabilities as victims of sexual violence without special attention from the State. Therefore, it is necessary to establish a new article to enforce legal protection for victims as well as their right to receive treatment, both short-term and long term after experiencing sexual violence and to increase the effectiveness of castration for perpetrators of sexual violence against persons with disabilities.